MECHANISMS FOR IMPROVING INNOVATION-ORIENTED MANAGEMENT METHODOLOGIES IN HIGHER EDUCATION - Rakhmonova Shakhlo Rashidovna (Galaxy International Interdisciplinary Research Journal, 2021)
Innovation management is a subject that raises the interest of academics and practitionersin the field of management. However, the academic literature is scarce regarding the detailsof implementing it in a systemic and routinised way. Additionally, although there aremultiple tools and models to apply it at a firm level, there is little information concerningits effectiveness. This article discusses the mechanisms for improving innovation-oriented management methodologies in higher education.